SDM Training Modules for Health and Social Care Professionals in Israel - Gutman, Carolyn; Cohen, Ayala; Redlich Amirav, Dorit (Frontiers in Psychiatry, 2021)
While the strategy of Shared Decision Making (SDM) originated in the medical field and was later adopted into the mental health arena, little attention has been paid to practice in the broader fields of the allied health and social care professions. These professions are grounded in the recognition of a need for practice that reflects the partnership and collaboration of the professional and the service user working together to further the health and wellbeing of the user. A pilot training module was developed to introduce and support students in their journey from exposure to the co-production ideology and the SDM strategy into clinical practice in the allied health and social care professions. The aim of the present article is to describe the students’ experiences while learning about SDM and their use of this knowledge in their field practice in Israel. The students’ experiences highlighted the complexity of integrating SDM into practice both at the individual student level as well as the macro environment. Moreover, it pointed to the need to further develop this co-production paradigm and the SDM strategy into the education of the allied health and social care professions.